Darifenacin Versus Parasacral Transcutaneous Electric Nerve stimulation for overactive bladder syndrome in patients infected with Human T-Lymphotropic Virus 1 – randomized open clinical trial - Tatiane Souza Soares de Oliveira; José Abraão C. Neto; Cassius José Vitor Oliveira; Néviton M. Castro; Edgar M. Carvalho (International Brazilian Journal of Urology)
ABSTRACT Purpose: To evaluate the efficacy of parasacral transcutaneous electric nerve stimulation (PTENS), in comparison to darifenacin for the reduction of OAB symptoms in patients infected with HTLV-1. Materials and Methods: This proof-of-concept randomized clinical trial was carried out at the HTLV-1 Outpatient Clinic of the University Hospital. Participants included 42 HTLV-1 infected subjects with symptoms OAB. The OAB symptoms score questionnaire (OABSS) was applied before and after treatment to evaluate each group: group1-received darifenacin and group 2-treated with PTENS. Random sequences and statistical analysis were generated by SPSS statistical package, version 27 (IBM Inc™). Results: There was no difference between groups regarding demographic, socio-economic and clinical characteristics. The initial median and interquartile (IQR) range of OABSS were 11.2 (9.5 - 14.0) in G1 and 10.7 (8.0 - 12.7) in G2. There was a reduction in the frequency, nocturia and urgency in both groups. However, 5 (23.8%) of the patients in the group treated with darifenacin abandoned the therapy, while only 1 patient (4,8%) stopped PTENS. Conclusions: Both protocols used in this study were effective in treating OAB syndrome and reducing OABSS. However, therapy abandonment and adverse events were more frequent in the darifenacin group compared to the PTENS group.